Assistance in Potato Donut Processing and Entrepreneurship in Podokoyo Village, Tosari District, Pasuruan - Asri, Tri Mega; Pratiwi, Amelia Ika; Sylvatri, Hapsari Dian; Putri, Debri Haryndia (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The primary objective of this community service program is to enhance the agricultural potential of Podokoyo tourist village by addressing the knowledge gap in potato processing. The program aims to equip the Family Welfare Development Women of Podokoyo Village with the skills and knowledge to transform potatoes, a local agricultural product, into high-value donut products. Method: The program is implemented in three stages: preparation, implementation, and evaluation. The preparation stage involves arranging the necessary equipment and facilities, ensuring space availability, and securing partner involvement and community support. The implementation stage is where the actual training takes place, and the participants learn to process potatoes into donuts. The evaluation stage assesses the effectiveness of the training and the participants’ ability to apply their new skills. Practical Applications: The practical outcome of this program is that the participants, the Family Welfare Development Women, are expected to be able to process potatoes into more valuable donut products. This not only adds value to the local agricultural produce but also contributes to the economic development of the Podokoyo village. Conclusion: The program has successfully achieved its goals, as evidenced by the improved abilities of the participants in financial management and adding value to their products. The success of the program is attributed to the availability of necessary equipment and facilities, partner involvement, and community support. This initiative has the potential to significantly improve the welfare of the rural communities in Podokoyo village.